2003
DOI: 10.1021/bi0346805
|View full text |Cite
|
Sign up to set email alerts
|

Protein Transduction Domains of HIV-1 and SIV TAT Interact with Charged Lipid Vesicles. Binding Mechanism and Thermodynamic Analysis

Abstract: Cell-penetrating peptides (CPPs) traverse cell membranes of cultured cells very efficiently by a mechanism not yet identified. Recent theories for the translocation suggest either the binding of the CPPs to extracellular glycosaminoglycans or the formation of inverted micelles with negatively charged lipids. In the present study, the binding of the protein transduction domains (PTD) of human (HIV-1) and simian immunodeficiency virus (SIV) TAT peptide (amino acid residues 47-57, electric charge z(p) = +8) to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
159
3
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(183 citation statements)
references
References 45 publications
18
159
3
3
Order By: Relevance
“…Previous detailed biophysical characterization of the structure and interactions of PTDs within membranes allowed important insights into the energetics of peptide translocation and the mechanisms of penetration processes (20,30,31). An especially well-studied PTD is the TAT peptide, and its cell penetrating capabilities have been characterized in detail (10 Numerous studies exist on the structures, which are adopted by PTDs in solution and in membranes, but not much is known about their mobility on or within membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous detailed biophysical characterization of the structure and interactions of PTDs within membranes allowed important insights into the energetics of peptide translocation and the mechanisms of penetration processes (20,30,31). An especially well-studied PTD is the TAT peptide, and its cell penetrating capabilities have been characterized in detail (10 Numerous studies exist on the structures, which are adopted by PTDs in solution and in membranes, but not much is known about their mobility on or within membranes.…”
Section: Discussionmentioning
confidence: 99%
“…These studies demonstrated that transmembrane potential is required for the peptides to be absorbed by neutral and charged lipid bilayer systems (Terrone, Sang et al 2003;Ziegler, Blatter et al 2003;.…”
Section: Current Studiesmentioning
confidence: 96%
“…However, the actual energy barrier for TAT binding to anionic membranes is almost certainly much lower, because the Wimley-White interfacial scale was derived for neutral POPC bilayers and thus does not include electrostatic attraction between cationic peptides and anionic lipids. Indeed, calorimetric studies of the binding energy of HIV TAT to 25% anionic membranes 113,114 reported a favorable free energy of À5.2 kcal/mol and 80% of which was estimated to be due to electrostatic interaction. In addition to electrostatic attraction, H-bonding of the guanidinium ions to the lipid phosphates and water, as detected in the NMR spectra, 6 must further contribute to the stabilization of TAT at the membrane-water interface.…”
Section: Free Energy Of Cpp Insertion Into Lipid Membranesmentioning
confidence: 99%
“…The high cationic density has several consequences. First, it drives CPP binding to the membrane surface, 113,114 after which Arg-phosphate interactions facilitate peptide insertion into the membrane by minimizing the exposure of the charged residues to the hydrophobic interior. Second, the Arg clusters can strongly interact with lipid headgroups on the distal surface of the bilayer to drive translocation.…”
Section: Mechanism Of Cpp Translocationmentioning
confidence: 99%